2021
DOI: 10.1155/2021/7435605
|View full text |Cite
|
Sign up to set email alerts
|

miR-129-5p Promotes Osteogenic Differentiation of BMSCs and Bone Regeneration via Repressing Dkk3

Abstract: Objective. Accumulating evidence indicates that microRNAs (miRNAs) play crucial roles in osteogenic differentiation. However, the associated mechanisms remain elusive. This paper is aimed at exploring the role of miR-129-5p in regulating bone marrow mesenchymal stem cell (BMSC) differentiation and bone regeneration in vivo and in vitro. Methods. BMSCs were transduced by miR-129-5p mimic, miR-129-5p inhibitor, and negative control lentivirus. The ability of BMSC differentiation to osteoblast was tested by alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…MiR-129-5p, located on p13, functions as a tumor obstructor to restrain malignant behaviors of cancer cells. MiR-129-5p plays a critical role in bone development, and miR-129-5p has been confirmed to promoter the differentiation of bone marrow mesenchymal stem cells [ 9 ]. Moreover, several reports have indicated that aberrant abundance of miR-129-5p is associated with multiple bone diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-129-5p, located on p13, functions as a tumor obstructor to restrain malignant behaviors of cancer cells. MiR-129-5p plays a critical role in bone development, and miR-129-5p has been confirmed to promoter the differentiation of bone marrow mesenchymal stem cells [ 9 ]. Moreover, several reports have indicated that aberrant abundance of miR-129-5p is associated with multiple bone diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Genepharma was procured for miRNA mimics and inhibitors (Shanghai, China). The vector, siRNA, miRNA mimics, and inhibitor were transfected into cells using lipofectamine 3000 (Thermo Fisher, USA) as previous study [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemical staining was followed by several revisions to the previous study [ 21 ]. The formalin-fixed and paraffin-embedded tissue were deparaffinated and washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Transfection of scramble control and OPRK1 siRNA (50 nM) (synthesized by GenePharma) in cells were performed according to the manufacturer’s instructions of Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%